Self-determination of Philosopher - K. Olimov; V.A. Bazhanov; B.V. Markov; A.M. Maksimov; R.Yu. Rakhmatullin; I.A. Belyaev; G.L. Tulchinsky; S.N. Nekrasov; A.I. Stoletov (Интеллект. Инновации. Инвестиции, 2019)
Within the framework of the correspondence round table, the multidimensional problem of the philosopher’s self-determination was discussed, which has a very high relevance. K. Olimov, raising the question of the philosopher’s self-determination, notes that this process unfolds under the influence of many internal and external factors. Pointing to thinkers who are the standards of worthy self-determination, he orients the philosophers of our day toward being objective researchers and spiritual mentors of his contemporaries. V.A. Bazhanov, reflecting on the importance of self-determination for the philosopher, stresses that it acquires special relevance under the influence of political factors. Raising the problem of the need for a philosopher and sharing his own experience of philosophical activity, he compares the specific features of the Soviet and post-Soviet reality. B.V. Markov focused on the actual problems of self-determination of the philosopher. Among them are: the peculiarities of the connection of philosophy with the national culture; the crisis of metaphysics and ontology, generating pluralism of cognitive practices; transformations of philosophizing techniques caused by significant changes in the realities of communicative culture; Actualization of critical theory discourses in the context of communicative humiliation. A.M. Maksimov, who considers philosophizing as an attribute of a person’s self-determination, writes about his “doom” for meaningful life thoughts, regardless of his cultural and educational level. He believes that the multidimensionality of the person himself and the process of his self-determination determines the complexity, ambiguity of establishing harmonious relations with his environment while preserving himself, his abilities to live honestly, bringing truth, goodness and justice into the world. R. Yu. Rakhmatullin, who focused on the problem of philosophical identity, connects it with the subject field of philosophy. Contouring the boundaries of philosophical identity, he proposes to recognize as its markers the validity of philosophical ideas, their ideological status and criticality. I.A. Belyaev, carrying out the differentiation of the divine-human and human-godly in the self-determination of the philosopher, stresses that his reasoning concerns only genuine thinkers who have dedicated their lives to comprehending and finding meanings. Denoting two alternative ways of self-determination of the philosopher, he characterizes their key features. G.L. Tulchinsky, who relates philosophy to science, shows that within the framework of the first of these, the finite being tries to understand the infinite world. In interpreting philosophy as ethos and self-determination, he draws attention to its out-of-nature and supernaturality and postulates the five consequences that flow from this: philosophy is freedom of choice; it is an individually unique reflection on reality; the philosopher has the opportunity to understand and judge this world, plunging into its context; philosophizing exhaustively comprehends the meanings of being with a rich palette of expressive possibilities. S.N. Nekrasov proceeds from the fact that philosophy is either a reflection of the world, or its construction, or reading, synthesizing the first and second in itself. In his reasoning, he seeks to show that the philosopher’s self-determination is the choice of a reading strategy, within the framework of which the operation of imputation is the most difficult for him, that is, attributing the ideas of the structure of the world to their social bases and class interests. A.I. Stoletov, in his reflections, relies on the idea that the era of the second “axial time” has now arrived, in connection with which philosophy has found itself on the verge of collapse, and its self-determination has become possible due to the identification and overcoming of boundaries. A philosopher who strives today for self-determination, enters into existential communication, is a lover with himself, another person, the world and God without the guarantee of the implementation of these processes.